2017
DOI: 10.1007/s11695-017-2901-5
|View full text |Cite
|
Sign up to set email alerts
|

Does Bariatric Surgery Affect the Incidence of Breast Cancer Development? A Systematic Review

Abstract: We reviewed the evidence for bariatric surgery reducing the risk of breast cancer. Data was extracted from multiple libraries, including PubMed, EMBASE, and Medline, to perform a systematic review. Abstracts were reviewed by two independent reviewers. Thirty-eight full-text articles were identified from 1171 abstracts. Four studies were included for meta-analysis; 114 of 10,533 (1.1%) patients receiving bariatric surgery versus 516 of 20,130 (2.6%) controls developed breast cancer, odds ratio 0.564 (95% CI 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 31 publications
3
20
0
2
Order By: Relevance
“…Morbidly obese women experienced significant increases in VBD following bariatric surgery at our institution, primarily related to substantial reductions in adipose volume. However, small yet significant reductions in FGV were also detected, suggesting that the decrease in FGV could be conveying the anticancer benefit previously described following bariatric surgery . This is in line with Shepard et al, which identified both FGV and percent FGV as stronger and more accurate predictors of breast cancer risk as compared to VBD …”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…Morbidly obese women experienced significant increases in VBD following bariatric surgery at our institution, primarily related to substantial reductions in adipose volume. However, small yet significant reductions in FGV were also detected, suggesting that the decrease in FGV could be conveying the anticancer benefit previously described following bariatric surgery . This is in line with Shepard et al, which identified both FGV and percent FGV as stronger and more accurate predictors of breast cancer risk as compared to VBD …”
Section: Discussionsupporting
confidence: 52%
“…Resolution and improvement of obesity‐related comorbidities, including diabetes mellitus and metabolic syndrome—two additional cancer risk factors—are also seen with surgical weight loss . Notably, multiple observational studies have additionally reported reductions in the incidence of several malignancies, including breast cancer, following bariatric surgery, possibly related to the decreased circulating estrogen levels seen with reductions in body fat . The impact of bariatric surgery on breast density as a potential modulator of cancer risk, however, remains poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations